A characterization of consistent assessments using power sequences of strategy profiles - Francesc Dilmé (International Journal of Game Theory, 2023)
This paper provides a new characterization of belief consistency in extensive games. We show that all consistent assessments are supported by sequences of strategy profiles with the property that all actions with vanishing probability are played according to power functions of the sequence index. The result makes it simpler to prove or disprove that a given assessment is consistent, facilitating the use of sequential equilibria.
Keywords: C72; C73; 330; Belief consistency; Sequential equilibria; Power sequences